Learning Objectives in ESP Books Based on Bloom’s Revised Taxonomy - Parsaei, Iraj; Alemokhtar, Mohammad Javad; Rahimi, Ali (Beyond Words, 2017)
University English books as the chief source of learning English are remarkably important and investigating their content quality can lead to English learning improvement. This study investigates learning objectives in ESP books for students of medicine, dentistry, and pharmacology in IUMS. Using Bloom’s taxonomy, learning objectives reflected in ESP books for students of medicine, dentistry, and pharmacology in IUMS were investigated in this library research. The frequency of each learning level used was determined. Descriptive statistics was used to depict the findings. of all the activities following each lesson in ESP books, only %8, %23, and %14 were aiming at improving higher cognitive levels of learning. There was no balance between applications of different learning levels throughout the books. Further studies are recommended to shed light on the issue. Key Words: Learning Objectives, Bloom's Revised Taxonomy, Textbook